1991
DOI: 10.1080/01431169108929719
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and spatial variability of aerosol optical depth in the Sahel region in relation to vegetation remote sensing

Abstract: A network of Sun photometers was established in the Sahel region of Senegal, Mali and Niger in order to monitor the aerosol characteristics needed for atmospheric correction of remotely sensed data. The aerosol optical thickness r. computed from the spectral Sun photometer measurements exhibited very high day-to-day variability ranging from approximately 0·1 to greater than 2·0 at 875 nm for both the wet and dry seasons. A gradient of decreasing r. from north-to-south latitudes in the Sahel for the wet season,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(35 citation statements)
references
References 22 publications
0
34
0
1
Order By: Relevance
“…The scatteringÅngström exponent (å sp ), estimated for 450 to 700 nm, decreases to near zero in this layer. It has been well documented thatå sp is inversely related to particle size (e.g., Eck et al, 1999;Schuster et al, 2006 and reference therein) and that values less than one are indicative of particles dominated by sea-salt and/or dust (e.g., Schuster et al, 2006;Holben et al, 1991). Tanré et al (2003) showed that theå sp values derived from Cape Verde AERONET observations were generally <0.2 during prevalent dust season, including August and September.…”
Section: Dust Layer Identificationmentioning
confidence: 99%
“…The scatteringÅngström exponent (å sp ), estimated for 450 to 700 nm, decreases to near zero in this layer. It has been well documented thatå sp is inversely related to particle size (e.g., Eck et al, 1999;Schuster et al, 2006 and reference therein) and that values less than one are indicative of particles dominated by sea-salt and/or dust (e.g., Schuster et al, 2006;Holben et al, 1991). Tanré et al (2003) showed that theå sp values derived from Cape Verde AERONET observations were generally <0.2 during prevalent dust season, including August and September.…”
Section: Dust Layer Identificationmentioning
confidence: 99%
“…Examining the daily mean spectral AODs in the light of the above, it has been found that α ( aerosol columnar size distributions dominated by fine mode aerosols (r < 1 µm), such as from biomass burning or urban/industrial activities (Holben et al, 1991;Westphal and Toon, 1991;Kaufman et al, 1992;Reid et al, 1999;, and 1.0 < α < 2 suggest the prevalence of mixed type of aerosols with significant contributions from both accumulation mode and coarse mode aerosols to the columnar AOD. The top panel of Fig.…”
Section: Spectral Aods and Their Wavelength Dependenciesmentioning
confidence: 99%
“…Five studies (Oluwafemi 1979, ben Mohamed & Frangi 1983, Fouquart et al 1987a, Faizoun et al 1994, Pinker et al 1994) have used sun photometers to make measurements at a single station. Studies by Cerf (1980), Holben et al (1991), d 'Almeida (1986'Almeida ( , 1987, ben Mohamed et al (1992) and Faizoun et al (1994) have some degree of spatial coverage, varying from 2 to 11 stations. In some cases, measurements are limited to a few months; many cover a 1 or 2 yr period at each station.…”
Section: Dustmentioning
confidence: 99%